Financial Development, ATM Penetration, and Economic Growth in West African Economies - Anastesia Uzonna Ezewulu; Vivian C. Onyejegbu (Journal of Social Science and Economics (JOSSE), 2026)
Despite sustained efforts to deepen financial systems in West Africa, economic growth outcomes have remained uneven, raising concerns about the effectiveness of financial development initiatives such as ATM expansion and credit provision to the private sector. Against this background, this study examined the relationship between financial development, ATM penetration, and economic growth in selected West African economies. The methodology is anchored on the extended Solow–Swan growth framework developed by Mankiw, Romer, and Weil, which incorporates human capital into economic growth analysis. The study specifies economic growth as a function of physical capital, human capital, financial development, and control variables, using a dynamic panel model. Data covering 16 West African countries (2004–2023) were analyzed with the System GMM estimator to address endogeneity and heterogeneity. Pre-estimation and post-estimation diagnostics ensured robustness, while variables were sourced from the World Bank, WGI, and UNDP databases. The correlation results show no severe multicollinearity, with pairwise coefficients generally below 0.80, except for RGDP–GFCF (0.8568). Cross-sectional dependence tests are significant (Pesaran = 3.409, p = 0.0007; Friedman = 41.567, p = 0.0001), justifying time effects in estimation. System GMM results indicate strong growth persistence, as lagged LOGRGDP is positive and significant (β = 0.994, p < 0.01). ATM spread negatively affects growth (β = −0.0054, p < 0.05). Domestic credit to the private sector is insignificant (β = −0.0004, p > 0.10). AR(2) (p = 0.435) and Hansen (p = 0.391) confirm model validity. Diagnostic tests confirmed instrument validity and model adequacy. The study concludes that financial infrastructure expansion alone is insufficient to drive growth without efficiency-enhancing reforms.